Modified textile waste for heavy metals removal - Patcharin Racho; Weesuda Waiwong (Energy Reports, 2020)
The performance of chemically modified textile waste for a heavy metal treatment is reported in this study. Two sorbents, which were prepared by a simple and concise method, were able to bind two heavy metals including Pb(II) and Cr(VI), with very high efficiencies. The binding mechanisms were studied through adsorption tests such as the influence of contact times, heavy metal concentrations as well as elution study. The overall results showed that the adsorption kinetics was very fast and attained an equilibrium within 180 min in all metals studied. The maximum single metal uptakes were 11.81 mg/g and 1.97 mg/g, for Pb(II) and Cr(VI), respectively. The sorbent could potentially be effective in treating large volumes of wastewater.
Keywords: 330; Amino chelating; Chemisorption; Graft copolymerization; Ion exchange; Modified textile; Textile waste